The advancement of Brazilian implantology and the Brazilian Journal of Implantology and Health Sciences. - Piattelli, Adriano (Brazilian Journal of Implantology and Health Sciences, 2020)
Dear friends of the Brazilian implantology and the Brazilian Journal of Implantology and Health Sciences, it is with great joy and enthusiasm that I come to congratulate and congratulate, on behalf of its Editor Dr Éber Coelho Paraguassu, the entire BJIHS editorial board. The existence of this new communication vehicle on implantology is one more lever for us to use in our favor and spread current and retrospective knowledge seriously and with quality. Even in the midst of this terrible COVID-19 epidemic that plagues my country, I still find motivation and courage to continue and move forward. I wish all BJIHS friends a lot of success and prosperity. Prof. A. Piattelli